The Humanitarian Consequences of western unilateral coercive measures on Syria - مرهج, عمار ياسين; نزار قنوع; عبير ناعسة (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aims to investigate and answer these questions: are western unilateral coercive measures effective in changing state behavior, or do they harm civilian populations more than governments? Prior studies on sanctions have almost exclusively focused on the economic impact that sanctions have on target states, whilst few have considered the consequences that they have on humanitarian conditions. This paper uses the case of Syria to evaluate the impact of sanctions on humanitarian conditions. we employ a process tracing methodology, and select three indicators (Economic Growth, Unemployment and Food Security) to chart changes in humanitarian conditions to determine whether the changes in the indicators may be due to sanctions. By examining humanitarian conditions in Syria five years before being sanctioned (2006-2011) to the sanction period of 2011-2020, this study unearths evidence that humanitarian conditions deteriorated because of sanctions in areas including: economic growth and reflections that on employments and food security.